Implantation and biomass of Avena sativa L., two methodologies of preparation, tillage soil and direct sowing - Beltramelli Gula, Marcos Osvaldo; Blanco Alves, Carlos Nicolas (Acta Iguazu, 2021)
Autumn sowing of oats and other winter species is the alternative to balance the annual dry matter production in Uruguay, with fast forage availability in 60 to 70 days and high nutritional quality. The objective of this research was to evaluate the implantation, biomass production and effect of soil compaction, on the production of oats in two soil conditions, intensive tillage and direct sowing, with two doses of fertilizer, in rain-fed. The experimental design was randomized blocks with 20 repetitions of 50x10cm for implantation and 18 repetitions of 7x4m, for biomass production. The cultivar used was La Estanzuela 1095a. It was determined: implantation of crop, biomass production and the resistance of soil to the penetration. The germination in tillage soil (TS) and direct sowing (DS), showed 91.7 and 76.6% emergence, respectively. The forage production showed no significant differences between TS and DS. The statistical analysis of the green matter data showed a significant difference between the treatments for the control plots and 50 units of nitrogen. The penetration resistance for the 1 cm-2 cone showed significant differences at 15 cm depth, while for the 5 cm-2 cone the significant differences were at all depths, with DS being greater. The TS treatment showed lower resistance to penetration, better implantation and greater biomass production.